Performance evaluation of inset feed microstrip patch antenna parameters with different substrate materials for 5G wireless applications - Kebbekoppalu Shrinivasa Praveena; M Patil Chandrashekar (Радіоелектронні і комп'ютерні системи)
This study evaluates the performance of an inset feed-microstrip antenna for various substrate materials (FR4, Rogers 5880, Rogers 6002, Polystyrene, and Ceramic) with different thicknesses (1.6 mm, 3.2 mm, and 4.8 mm) for 5G applications, focusing on key parameters such as return loss, efficiency, directivity, and realized gain. The goal is to determine the optimal substrate material and thickness that offers the best combination of these performance metrics across a frequency range of 3 to 4 GHz. The proposed method uses a new hybrid GA-PSO algorithm with Dynamic Adaptive Mutation and Inertia Control (DAMIC). The study optimized the MSPA design for each material and thickness, followed by detailed simulations using the Advanced System Design (ADS) tool. The approach included parametric analysis and systematic comparisons across the chosen substrate materials, quantifying their performance using specified metrics. Results indicate that Rogers 5880 consistently outperforms other substrates in terms of efficiency, directivity, and gain across all thicknesses. Polystyrene and Rogers 6002 also exhibited commendable performance, especially in the thicker substrates (3.2 mm and 4.8 mm), with Polystyrene achieving the highest directivity at 4.8 mm thickness. Rogers 5880 again led the performance in terms of efficiency, with efficiency values consistently above 70 % across all thicknesses, peaking at 86.38 % at 1.6 mm and 86.39 % at 3.2 mm. Ceramic and FR4 substrates demonstrated relatively lower performance, with Ceramic showing a moderate peak efficiency of 75.98 % at 1.6 mm and 50.79 % at 3.2 mm, while FR4 consistently had the lowest efficiency and directivity values, highlighting its limitations for high-performance antenna applications. Considering the return loss, the Rogers 5880 displayed the most favorable return loss characteristics, maintaining values well below -10 dB across the frequency range, which signifies excellent impedance matching. Rogers 6002 and Polystyrene also showed acceptable return loss characteristics although slightly higher than Rogers 5880, and they remained below 10 dB for most frequencies. Ceramic and FR4 exhibited higher return loss values, suggesting poorer impedance matching and higher signal reflection. In conclusion, The GA-PSO DAMIC optimization technique is a highly effective approach for designing antennas for 5G systems, enabling customized solutions for various substrates. Unlike traditional methods, the GA-PSO DAMIC approach enables precise tuning of key antenna parameters—return loss, gain, directivity, and efficiency—across various substrate configurations and thicknesses. The results demonstrate that the Rogers 5880 substrate, particularly at a thickness of 1.6 mm, consistently offers superior performance metrics, including high efficiency and low return loss, confirming its suitability for 3-4 GHz 5G applications. The results also reveal that Rogers 5880 is the superior substrate for high-frequency applications requiring high efficiency, directivity, and gain, followed by Polystyrene and Rogers 6002, particularly for thick substrates. Ceramic and FR4, although adequate in certain scenarios, are generally less optimal for high-performance requirements because of their lower efficiency and higher return loss. These findings provide critical insights into antenna design and material selection, emphasizing the significance of substrate choice in achieving desired performance metrics in modern RF 5G applications.